Analisis Peran SDM dalam Pelaksanaan Budaya K3 di UMKM Konveksi Mamah Wulan Cangkuang Kab Bandung - Astriani Saputri; Leli Nirmalasari (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Occupational health and safety (OHS) is vital for sustainable workplace productivity yet its adoption within MSME remains limited. This qualitative descriptive study explores the human resource function in executing OHS culture at the Mamah Wulan garment MSME in Cangkuang, Bandung regency. Data were gathered from nine purposively selected informants through interviews, observation and documentation. Then analyzed using the Miles, Huberman, and Saldaña interactive model with source triangulation. The findings reveal that while lighting, the physical environment, and psychological factors favor OHS culture, several obstacles persist. They include inconsistent PPE compliance, missing written SOP, weak supervision and physical exhausting during production surges. Ultimately the study highlights that enhancing human resource’s role through ongoing oversight, training and documented procedures is crucial to sustain OHS implementation.